2010
DOI: 10.1186/1471-2229-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of beta-tubulin regions defined by antibodies on an Arabidopsis thalianamicrotubule protofilament model and in the cells

Abstract: BackgroundThe function of the cortical microtubules, composed of αβ-tubulin heterodimers, is linked to their organizational state which is subject to spatial and temporal modulation by environmental cues. The role of tubulin posttranslational modifications in these processes is largely unknown. Although antibodies against small tubulin regions represent useful tool for studying molecular configuration of microtubules, data on the exposure of tubulin epitopes on plant microtubules are still limited.ResultsUsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
(68 reference statements)
1
18
1
Order By: Relevance
“…2D), suggesting that the two Tyr residues are major phosphorylation sites for CRK2, CRK3, and CRK8. Interestingly, Tyr phosphorylation of ␤-tubulins in Arabidopsis and tobacco plants has already been reported (12,30,31). Our finding suggests that the three CRKs are the responsible PKs for Tyr phosphorylation of ␤-tubulins.…”
Section: Identification Of Tyr Autophosphorylation Protein Kinases Ussupporting
confidence: 71%
See 1 more Smart Citation
“…2D), suggesting that the two Tyr residues are major phosphorylation sites for CRK2, CRK3, and CRK8. Interestingly, Tyr phosphorylation of ␤-tubulins in Arabidopsis and tobacco plants has already been reported (12,30,31). Our finding suggests that the three CRKs are the responsible PKs for Tyr phosphorylation of ␤-tubulins.…”
Section: Identification Of Tyr Autophosphorylation Protein Kinases Ussupporting
confidence: 71%
“…Previous studies have already shown that the Tyr residues of ␣-and ␤-tubulin are phosphorylated in Arabidopsis and tobacco, but the phosphorylation site(s) and the kinases responsible for phosphorylation remain unknown (30,31). By pulldown assays using protein lysate from cultured cells and in vitro kinase assays, we identified the Tyr residues of TBB7 that are phosphorylated by CRK2, CRK3, and CRK8.…”
Section: Discussionmentioning
confidence: 93%
“…The authors proposed that the degree of tyrosine phosphorylation of -tubulin after the cells' exposure to inhibitors of tyrosine kinases and tyrosine phosphatases is an important factor to determine the state of assembly of microtubules in animal cells [40]. Recently using double-label staining experiments on A. thaliana microtubules with a polyclonal anti-phosphotyrosine antibody (P-Tyr), a monoclonal anti--tubulin (TU-01) and an anti--tubulin antibody (TUB 2.1) it was shown that phosphotyrosine labeling correlated with cortical microtubules in interphase cells as well as with all types of mitotic microtubules [20]. It was also estimated that the signal detected with the anti-phosphotyrosine antibody was markedly enhanced after pretreating the cells with sodium orthovanadate, as compared with control (untreated) cells.…”
Section: Effects Of Tyrosine Kinases and Tyrosine Phosphatase Inhibitmentioning
confidence: 99%
“…Recently it was established that both -and -tubulins undergo phosphorylation on tyrosine residues [19]. Immunofluorescence microscopy revealed that tyrosine phosphorylation of -tubulin could be one of the targets for tyrosine kinases [20]. In our previous paper we have provided data that tyrosine kinase inhibitors as herbimycin A, genistein and tyrphostin AG18 as well as an inhibitor of tyrosine phosphatases, sodium orthovanadate, affect microtubule organization in Arabidopsis thaliana root cells.…”
mentioning
confidence: 99%
“…124 Involvement of PTKs and PTPs in the organization of microtubules in primary root cells was shown using specific inhibitors. 46,125 Other components of cytoskeleton are also modulated by Tyr phosphorylation. For example, in Mimosa pudica, Tyr phosphorylation of actin is induced by stimulation of the pulvinus and its stimulation is abolished by PAO.…”
Section: Acknowledgmentsmentioning
confidence: 99%